An experimental study on the blast responses of hollow core concrete slabs to contact explosions - Savas, Sedat; Bakir, Dursun (Pontificia Univ Catolica Chile, Escuela Construccion Civil, 2022)
Measures taken against preventing damages in structures against explosive load are a popular matter of investigation among researchers. Generally, numerous studies were conducted on reinforcement materials for outer surfaces, reinforcement design, and utilizing fibers produced from various materials. In this study, a hollow-core slab was manufactured with concrete, which had a regular strength, and a design that discharged the explosive energy upon contact explosion via the hollow cores of the slabs and prevented the redirection of the explosive energy to the area below the slabs was investigated. Because the hollow-core slab in the study did not have any lateral reinforcement, the utilization of the tensile strength of the concrete proved advantageous. For this purpose, in the experimental tests of the study, contact explosions were conducted on hollow-core slabs with hollow diameters of 14 cm for each core. Before the explosion tests, the TNT equivalent of 910gr explosive was determined by performing the TNT equivalent tests. In the explosion tests of prepared hollow core concrete slabs, 125 gr, 250 gr, 375 gr, and 500 gr dynamites were used as the explosive materials. In conclusion, the explosive loads that the slabs could withstand were calculated and various slabs with distinctive hollow-core diameters were determined depending on the amount of the explosives.
Keywords: Contact explosion; explosive pressure; hollow-core slab; crater hole; absorption of explosive pressure